2011
DOI: 10.1007/s00396-011-2515-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phase structures and surface free energy values for the coatings synthesised from linear polyurethanes and from waterborne polyurethane cationomers

Abstract: WAXS, DSC and AFM methods were employed to compare phase structures of the coatings obtained from waterborne polyurethane cationomers which had been synthesised in the reaction of some diisocyanates (MDI, IPDI, TDI and HDI) with polyoxyethylene glycols (M = 600 and 2,000) and butane1,4-diol or N-methyl- or N-butyldiethanolamine and 2,2,3,3-tetrafluoro-1,4-butanediol. The structures were also analysed of the coatings derived from linear polyurethanes which had been synthesised on the basis of similar raw materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 26 publications
0
12
0
2
Order By: Relevance
“…Cation‐containing polyurethanes, or polyurethane cationomers, are an important class of polyurethane ionomers, which have found wide applications in protective coatings, biocides, antistatic agents, antimicrobial nanofilters, and polymeric colorants 1–3. A typical synthesis of polyurethane cationomers involves a tertiary amine‐containing diol as the chain extender and a subsequent alkylation of tertiary amine to generate ammonium cations.…”
Section: Introductionmentioning
confidence: 99%
“…Cation‐containing polyurethanes, or polyurethane cationomers, are an important class of polyurethane ionomers, which have found wide applications in protective coatings, biocides, antistatic agents, antimicrobial nanofilters, and polymeric colorants 1–3. A typical synthesis of polyurethane cationomers involves a tertiary amine‐containing diol as the chain extender and a subsequent alkylation of tertiary amine to generate ammonium cations.…”
Section: Introductionmentioning
confidence: 99%
“…16) in a vacuum drier, at 80 °C, over 6 h, followed by additional conditioning by exposure to ambient air during 10 days. The detailed information on polyurethane synthesis conditions was presented in our earlier paper [14]. The results of mechanical tests for these coatings confirm that the synthesised materials are elastomers and that their strength at about 40 MPa and elongation at a break of 40 % is sufficient for protective coatings.…”
Section: Methodsmentioning
confidence: 53%
“…Those impacts result from the presence of hydrogen bonds, from polarity of segments and their susceptibility to dispersion interactions. Our earlier WAXS investigations revealed that the obtained (applied) polyurethane coats contained max up to 20 % of crystalline phase which was composed principally of hard segments [14]. It is hence the polyurethane chemical structure to be critical for SFE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous articles have described the chemistry and processes used to manufacture PU [5][6][7]. The effects of various factors such as the structure and content of diisocyanates, polyols, hydrophilic groups and chain extenders on the preparation and properties of PU dispersions have been studied extensively [8][9][10][11][12]. Additionally, thermal phase separation and the physical properties of PU prepared from different polyols have also been investigated [13,14].…”
Section: Introductionmentioning
confidence: 98%